2009
DOI: 10.1002/dmrr.953
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exclusive breastfeeding reduces autoimmune diabetes incidence and increases regulatory T‐cell frequency in bio‐breeding diabetes‐prone rats

Abstract: Prolonged exclusive breastfeeding partially protects BBDP rats from autoimmune diabetes development. Interestingly, ingestion of solid food during the weaning period completely abolishes this protective effect. The protective effect of exclusive breastfeeding correlates with higher levels of naturally occurring regulatory T cells throughout life and low cytokine secretion at weaning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…We observed a significant prevention in reduction of this enzyme activity in the 21‐day‐old pups, whose mothers were treated with Met + Mel, suggesting that the youngest pups who were nursing until this age had maternal protection. A study showed that nursing improves immunity and prevents offspring diseases: prolonged exclusive breastfeeding reduces autoimmune diabetes incidence and increases regulatory T‐cell frequency in bio‐breeding diabetes‐prone rats (Brugman et al, 2009). Our results suggested that melatonin treatment may be sufficient to prevent detectable damage through 21 days but not through 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a significant prevention in reduction of this enzyme activity in the 21‐day‐old pups, whose mothers were treated with Met + Mel, suggesting that the youngest pups who were nursing until this age had maternal protection. A study showed that nursing improves immunity and prevents offspring diseases: prolonged exclusive breastfeeding reduces autoimmune diabetes incidence and increases regulatory T‐cell frequency in bio‐breeding diabetes‐prone rats (Brugman et al, 2009). Our results suggested that melatonin treatment may be sufficient to prevent detectable damage through 21 days but not through 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Formula feeding has been associated with various inflammatory and autoimmune diseases. 37 In contrast, breastfeeding, through its effects on the microbiome, has been associated with a protective role against asthma, autism spectrum disorder, and type 1 diabetes. 27,37 …”
Section: Environmental Factorsmentioning
confidence: 99%
“…Additional candidate mechanisms may involve reduced gut permeability, induction of the maturation of regulatory T cells in the gut-associated lymphoid tissue and/or modification of the gut microflora. Supporting these possibilities, it was shown that a highly hydrolyzed formula induced a decrease in autoimmune diabetes in the diseaseprone BioBreeding rat, in association with improved integrity of the intestinal barrier, production of regulatory cytokines and beneficial changes in gut microflora [32,33]. It is also possible that other elements of diet diversification such as cereal proteins may be at play, as suggested by some animal models [34,35].…”
Section: Which Are the Environmental Factors At Play?mentioning
confidence: 95%